KESIAPAN SPAM REGIONAL KARTAMANTUL DI KABUPATEN SLEMAN: STUDI PADA 4 SPAMDES - Endiarjati Dewandaru Sadono; Amirullah Setya Hardi; Bintang Prasodjo (Jurnal Kawistara, 2018)
SPAM Regional Kartamantul is one of the steps of Special Region of Yogyakarta Government to realize the RPJMN 2015-2019 in the provision of drinking water for 100 percent of the population in 2019. Because Sleman District is one of the areas included in SPAM Regional Kartamantul, this study seeks to identify the readiness of 4 SPAMDes in this district to welcome SPAM Regional Kartamantul. The results of this study are expected to be descriptive assessment of the readiness of those Regional SPAM. This study identified that some SPAMDes are still not ready to be integrated with SPAM Regional Kartamantul. In the future, the ready SPAMDes should be directed to cooperate with or be formed into BUMDes. In adittion, clear tariff arrangements are required for entrepreneurs of fishing ponds, laundry or car washers, whether they are subject to progressive rates or are not allowed to become SPAMDes customers. Nevertheless, there are still a subjective element of the Chairman of PERPAMDES Association that determines the successful and unsuccessful SPAMDes. Therefore, we suggest that in the next study the standard indicators needs to be identified so that the subjective element can be reduced.